2013
DOI: 10.1063/1.4789268
|View full text |Cite
|
Sign up to set email alerts
|

Global sampling of the photochemical reaction paths of bromoform by ultrafast deep-UV through near-IR transient absorption and ab initio multiconfigurational calculations

Abstract: Ultrafast deep-ultraviolet through near infrared (210-950 nm) transient absorption spectroscopy complemented by ab initio multiconfigurational calculations offers a global description of the photochemical reaction pathways of bromoform following 255-nm excitation in methylcyclohexane and acetonitrile solutions. Photoexcitation of CHBr3 leads to the ground-state iso-CHBr3 product in a large quantum yield (∼35%), formed through two different mechanisms: concerted excited-state isomerization and cage-induced isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 111 publications
3
44
0
Order By: Relevance
“…This isomerization pathway could be termed 'roamingmediated', because it involves the migration of the incipient bromine fragment and leads to the iso product species; however, this could not be confirmed without comparison to the same reaction in the gas phase. The isomeric form occupies a shallow minimum on the potential energy surface (PES)-somewhat below the C-Br bond radical dissociation asymptote [12][13][14][15] -and has been proposed 16 to be accessible on the way towards molecular bromine from photoexcited bromoform in the gas phase. This isomerization pathway in the gas phase can only occur through the internal rearrangement of atoms, that is, directly and without the involvement of any other species.…”
mentioning
confidence: 99%
“…This isomerization pathway could be termed 'roamingmediated', because it involves the migration of the incipient bromine fragment and leads to the iso product species; however, this could not be confirmed without comparison to the same reaction in the gas phase. The isomeric form occupies a shallow minimum on the potential energy surface (PES)-somewhat below the C-Br bond radical dissociation asymptote [12][13][14][15] -and has been proposed 16 to be accessible on the way towards molecular bromine from photoexcited bromoform in the gas phase. This isomerization pathway in the gas phase can only occur through the internal rearrangement of atoms, that is, directly and without the involvement of any other species.…”
mentioning
confidence: 99%
“…4 to account for the experimental observations. Pal et al 25 recently argued for a direct route to iso-bromoform via a conical intersection from the S1 state of photoexcited CHBr3, but we have no direct (experimental or theoretical) evidence for such a pathway in CCl4 so have not included it in the scheme. with CCl3 either as a fast geminate recombination process, or after diffusion, which is suggested to take hundreds of nanoseconds 18,23,39 and is therefore unlikely to be important on the timescale of this work.…”
Section: Photochemical Reaction Scheme For Ccl4mentioning
confidence: 99%
“…Isomeric (iso) forms of the parent compound have been extensively characterised in several photolysis studies of halomethanes in matrices and in liquids, 24,25,42,43 and shown to give rise to broad, strong visible absorption bands. A recent computational study of CHBr3 isomerization showed significant charge-separation character in iso-CHBr2-Br, which exhibits mixed covalent and ionic character, with (CHBr2) + Br -contributing the major (62%) resonance structures.…”
Section: Uv and Visible Absorption Band Assignmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The signal output of a TOPAS (LightConversion) optical parametric amplifier was used to generate 1300 nm excitation ("pump") pulses with the energy of 40 μJ pulse −1 . A white-light continuum in the 340−760 nm spectral range was used for probing.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%